The Historical Criticism in The Women in the Castle by Jessica Shattuck - Salsabila, Arih (English Literature Study Program, 2023)
World War II occurred in Germany between 1933 and 1945, under the rule of Hitler and the Nazis, pitting Germany against the Allies. Propaganda played a significant role in their efforts to secure victory. Propaganda was employed to manipulate the perceptions and positions of various groups to align with the Nazis' agenda. This study focused on the forms of propaganda used by the Nazis against Non-Aryan groups, including Gypsies, Slavs, Jews, and Polish. It also explored how German society responded to this propaganda during the period of 1933-1945, as depicted in Jessica Shattuck's novel